The Role of Physical Exercise to Improve the Browning of White Adipose Tissue via POMC Neurons - Rodrigues, Kellen C. da Cruz; Pereira, Rodrigo M.; Campos, Thaís D. P. de; Moura, Rodrigo F. de; Silva, Adelino S. R. da; Cintra, Dennys E.; Ropelle, Eduardo R.; Pauli, José R.; Araújo, Michel B. de; Moura, Leandro P. de (Frontiers in Cellular Neuroscience, 2018)
Obesity is a public health issue that affects more than 600 million adults worldwide. The disease is characterized by fat accumulation, mainly in the abdominal area. The human body is mainly composed of two types of adipose tissue: white adipose tissue (WAT) and brown adipose tissue (BAT); however, the browning process generates a different type of brown fat-like adipocyte in WAT, which similar to BAT has thermogenic capacity by activating UCP-1. The hypothalamic arcuate nucleus plays an important role in WAT browning via POMC neurons, which are influenced by synergistic insulin and leptin signaling. On the other hand, stimulation of AgRP neurons suppresses WAT browning. The hypothalamic inflammatory process that occurs in obesity impairs insulin and leptin signaling in this tissue and, consequently, can decrease WAT browning. In addition, practicing physical exercise may be a great strategy for triggering the browning process since it reduces hypothalamic inflammation and increases POMC neurons gene expression. Moreover, physical exercise stimulates irisin gene expression, which has an important impact on thermogenesis, which in turn culminates in increased gene expression of proteins such as UCP-1 and Cidea, which are related to WAT browning. Furthermore, thermogenetic activation of WAT leads to increased energy expenditure, favoring obesity treatment. Therefore, this mini-review aimed to highlight the most recent studies that link the control of hypothalamic activity with the browning metabolism of adipose tissue in response to physical exercise.